2016
DOI: 10.1177/0829573516644901
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent Group Contingency to Promote Physical Activity in Children

Abstract: As the number of children affected by obesity increases in the United States, it is necessary to intervene with preventive and intervention techniques that will enact change. Because children spend a significant amount of their time in school, it is of particular interest to target strategies during the school day. Given the recommendations for the total duration and intensity of physical activity children should participate in, recess period is a means of acquiring a portion of this daily recommendation. Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…In all the GC conditions, the step counts at post-intervention increased by approximately 2,700 steps (48.35%), compared with the baseline. These results are consistent with the findings from several traditional, face-to-face studies (Vidoni et al, 2014;Kuhl et al, 2015;Foote et al, 2017), and recent studies demonstrating the effectiveness of technology-based GC to promote physical activity (Patel et al, 2016a). In GC, participants are classified into a group where target behavior, reinforcement criterion, and reinforcers are all identical.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In all the GC conditions, the step counts at post-intervention increased by approximately 2,700 steps (48.35%), compared with the baseline. These results are consistent with the findings from several traditional, face-to-face studies (Vidoni et al, 2014;Kuhl et al, 2015;Foote et al, 2017), and recent studies demonstrating the effectiveness of technology-based GC to promote physical activity (Patel et al, 2016a). In GC, participants are classified into a group where target behavior, reinforcement criterion, and reinforcers are all identical.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of the maintenance effect of the intervention, step counts of participants regressed to the baseline level at follow-up. Such decrease in behavior following the withdrawal of reinforcement has been reported in previous research that examined the effectiveness of GC (Patel et al, 2016a;Foote et al, 2017) or other types of CM in promoting physical activity (Finkelstein et al, 2008;Patel et al, 2016bPatel et al, , 2018Weinstock et al, 2016). In contrast, some other studies, which have also examined the effectiveness of CM in promoting physical activity (Hunter et al, 2013;Petry et al, 2013) or drug discontinuation (Epstein et al, 2003;García-Fernández et al, 2011;Secades-Villa et al, 2011;Petitjean et al, 2014), have reported sustained effects even months after termination of the intervention.…”
Section: Discussionmentioning
confidence: 52%
“…Noise level was defined as magnitude of sound, measured in decibels (e.g., Davey, Alexander, Edmonson, Stenhoff, & West, 2001). Exercise was defined as the percentage of time participating in exercise, number of exercises completed, or duration of time spent exercising (e.g., Allen & Iwata, 1980; Foote, 2010). Any study that did not fit into one of the above categories was coded as other.…”
Section: Methodsmentioning
confidence: 99%
“…Since group contingencies target the behaviour of individuals in a group simultaneously, it is not surprising that teachers have reported group contingencies are effective and acceptable to use with their students (Alric et al, 2007;Donaldson et al, 2018;Hartman & Gresham, 2016;Lynch et al, 2009;Theodore et al, 2001;Theodore et al, 2004). This is likely why group contingencies have been implemented in various locations within the school, such as the academic classroom (Barrish et al, 1969;Beeks & Graves, 2016;Brantley & Webster, 1993;Briesch et al, 2013;Bulla & Frieder, 2018;Caldarella et al, 2015;Christ & Christ, 2006;Clair et al, 2018;Dart et al, 2016;Foley et al, 2019;Groves & Austin, 2017;Hansen & Lignugaris/Kraft, 2005;Hawkins et al, 2017;Heering & Wilder, 2006;Jones et al, 2008;Lum et al, 2019;Pokorski et al, 2019;Trevino-Maack et al, 2015;Williamson et al, 2009), gym class (Normand & Burji, 2020;Vidoni & Ward, 2006;Vidoni et al, 2012;Vidoni et al, 2014), hallway (Campbell & Skinner, 2004;Deshais et al, 2018), cafeteria (Williamson et al, 1992), and recess (Foote et al, 2017;Galbraith & Normand, 2017).…”
Section: Group Contingenciesmentioning
confidence: 99%
“…The vast majority of group contingency research in schools has focused on the evaluation of the IGC. Researchers have demonstrated the effectiveness of the IGC to increase behaviours such as class participation (Cheatham et al, 2017), on-task behaviour (Denune et al, 2015;Leflot et al, 2013;Pennington & McComas, 2017), academic engagement (Caldarella et al, 2015;Christ & Christ, 2006;Clair et al, 2018;Collins et al, 2017;Hernan et al, 2019;Popkin & Skinner, 2003), social and supportive interactions (Groves & Austin, 2017;Kohler et al, 1990;Popkin & Skinner, 2003), homework completion and accuracy (Little et al, 2010;Reinhardt et al, 2009), and physical activity (Foote et al, 2017;Galbraith & Normand, 2017;Kuhl et al, 2015;Normand & Burji, 2020). Researchers have also demonstrated the effectiveness of the IGC to decrease behaviours such as inappropriate behaviour (Barrish et al, 1969;Donaldson et al, 2011;McGoey et al, 2010), off-task behaviour (Clair et al, 2018), disruptive behaviour (Beeks & Graves, 2016;Caldarella et al, 2015;Christ & Christ, 2006, Clair et al, 2018Foley et al, 2019;Groves & Austin, 2017), transition time between classes (Campbell & Skinner, 2004;Hawkins et al, 2015), and cell phone use during class (Hernan et al, 2019;Jones et al, 2019).…”
Section: Interdependent Group Contingency (Igc)mentioning
confidence: 99%